The effect of virtual reality-based treadmill gait training on functional mobility and balance in chronic stroke patients: a randomized controlled trial - Seung-Hyeon Han; Hyeon Ju Jang; Jong Weon Lee; Jong Weon Lee; Jin Woong Cheong; Young Dae Kim; Hyo Suk Nam; Deog Young Kim; Deog Young Kim (Frontiers in Neurology)
IntroductionStroke is a leading cause of long-term disability worldwide. Chronic stroke survivors experience gait and balance impairments, limiting mobility and increasing fall risk. Treadmill training improves walking speed and endurance but lacks real-world adaptability. Virtual reality (VR)-based treadmill training offers immersive, task-specific practice, potentially improving functional mobility in real environments. This randomized controlled trial, using a prospective, open, blinded end-point (PROBE) design, aimed to evaluate the effects of VR-based treadmill gait training on gait performance, functional mobility, balance, and gait symmetry compared with conventional physical therapy in individuals with chronic stroke.MethodsThirty chronic stroke patients were randomly assigned to virtual reality treadmill training (VTT) or conventional therapy (CT) groups. Both groups received 30 min of conventional therapy twice weekly for 6 weeks. The VTT group received an additional 30 min of VR-based treadmill training per session using the C-Mill VR+ system, including obstacle negotiation and velocity modulation. The 10-meter walk test (10MWT), 6-min walk test (6MWT), Timed Up and Go (TUG) test, Dynamic Gait Index (DGI), Performance-Oriented Mobility Assessment (POMA), Berg Balance Scale (BBS), asymmetry of spatiotemporal gait parameters, and center of pressure (CoP) sway velocity were assessed pre- and post-intervention.ResultsWalking speed during the 10MWT and the 6MWT significantly increased in the VTT group compared to the CT group, and asymmetric index values for stance and swing duration decreased (p < 0.05). TUG test time, DGI values, and the POMA gait component were significantly improved in the VTT group compared to the CT group (p < 0.05). BBS scores and CoP sway velocity for eyes open and tandem stance conditions also significantly improved (p < 0.05).ConclusionThis study demonstrated that VR-based treadmill gait training effectively improved gait performance, functional mobility, balance, and gait symmetry in chronic stroke patients. Thus, simulating diverse virtual walking environments in a controlled setting can improve functional benefits in individuals with chronic stroke and potentially reduce fall risk in real-world community and home environments.Clinical Trial Registrationhttps://clinicaltrials.gov/study/NCT06557681?term=NCT06557681&rank=1, Identifier: NCT06557681.